PENGUKURAN KINERJA KEUANGAN DAERAH DAN PERTUMBUHAN EKONOMI BERBASIS RASIO PEMERINTAH KOTA MEDAN - Oktarini Khamilah Siregar (Jurnal Akuntansi Bisnis dan Publik, 2018)
Medan City is a metropolitan Municipal Government where its territory has an increasing number of people every year to confuse the local government in the development of the area. On the other hand the allocation of available development funds is relatively limited so the government should be able to facilitate the needs of the community for sustainable development. So the Government should be able to grow new investment in Medan City through allocation of revenue fund such as income, debt and expenditure so as to increase economic growth. This research uses LKPD data of Medan and Medan in figures from 2006 to 2015, then data is processed using SPSS method. The results of this data analysis can prove that partially Debt Ratio to GDP, Debt Ratio to Local Revenue, Debt Servica Ratio, Debt Ratio to Local Revenue, Growth Analysis of Spending no effect and significant to economic growth (GDP in constant price). While the Ratio of Efficiency Expenditure, Ratio of Regional Expenditure to PDRB partially influence to economic growth (GDP in constant price). Then Simultaneous Debt Ratio to GRDP, Debt Ratio to Local Revenue, Debt Servica Ratio, Ratio of Debt to Local Revenue, Expense Growth Analysis, Expense Efficiency Ratio, Ratio of Regional Expenditure to GRDP affect economic growth (GDP in constant price). With the influence of 98.50% Debt to GDP ratio, Debt Ratio to Local Revenue, Debt Servica Ratio, Revenue Ratio to Local Revenue, Growth Analysis of Expenditure, Expense Efficiency Ratio, Local Expenditure Ratio to GRDP in constant price while the remaining 0.50 % is explained by other factors such as regional financial dependency ratio, debt growth analysis, revenue and expense realization analysis and other financial performance ratios. With the management of optimal regional financial performance such as effectiveness in the use of expenditure and income efficiency can increase economic growth (PDRB in constant price) in Medan City.